A mapping review of challenges in existing technology-based occupational safety training in the tourism and hospitality industry: Research potential in commercial kitchens - Saad, Mazni; Sahrir, Muhammad Sabri; Abdullah, Norhidayah; Jeinie, Mohammad Halim; Mokhtar, Mohd Khalid (International Journal of Occupational Safety and Health, 2024)
Introduction: An effective response to a safe and healthy work environment relies on advanced preparedness such as occupational safety training. The main objectives of this study are to describe and classify the most critical challenges and identify knowledge gaps in the literature that could inform future research. Methods: For methods, a mapping review gathers information from six search engines; Francis and Taylor, Scopus, Science Direct, Emerald Insight, and SpringerLink, which yielded journal publications between 1948 and 2022. The data were analyzed using meta-analysis from 135,310 article search results, whereby 20 articles met the inclusion criteria. The studies varied in terms of aim, study design, and reporting detail. Results: The results showed that Canada and the United States are countries that study safety training in the tourism or hospitality industry, mainly in food management and food safety. The results also show that studies on occupational safety training in commercial kitchens are not common in the existing literature. The findings revealed that the highest number of articles involving safety training focused on food safety and food management in the tourism industry but less on kitchen workers' safety. Conclusion: In conclusion, this mapping review demonstrates hospitality workers' struggles, especially commercial kitchen workers. This review presents the types of technologies used for occupational safety training and provides an overview of different strategies that address the challenges. Among the most significant obstacles in occupational safety and health training is a lack of knowledge, the high financial costs for implementation, and outdated policies from authorities.